2012
DOI: 10.1530/joe-11-0455
|View full text |Cite
|
Sign up to set email alerts
|

The aging myostatin null phenotype: reduced adiposity, cardiac hypertrophy, enhanced cardiac stress response, and sexual dimorphism

Abstract: The natural aging process results in the physiological decline of multiple tissues and organ systems. Changes commonly occur with middle age and include decreased skeletal muscle mass, bone mineral density, cardiac output, and insulin sensitivity, and increased adiposity, all of which can contribute to the onset of sarcopenia, osteoporosis, heart failure, or type 2 diabetes. Recent studies suggest that myostatin may influence many of these systems. We therefore sought to determine whether they are affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 58 publications
8
48
0
Order By: Relevance
“…Knocking out of myostatin resulted in decreased weight of fat, liver, and kidney as proportional to body weight (18,19,26,32). The absolute weight of heart increased; however, heart weight/body weight ratio did not change (19,26). Bünger et al (8) introgressed the Compact mutation into a mouse line with extreme growth (DUHi).…”
Section: Discussionmentioning
confidence: 99%
“…Knocking out of myostatin resulted in decreased weight of fat, liver, and kidney as proportional to body weight (18,19,26,32). The absolute weight of heart increased; however, heart weight/body weight ratio did not change (19,26). Bünger et al (8) introgressed the Compact mutation into a mouse line with extreme growth (DUHi).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] However, previous studies uncovered a correlation of reduced myostatin activity with early lethality in cattle 37 and demonstrated that inactivation of myostatin in laminin-deficient dyW/ dyW mice leads to early postnatal death. 38 We assume that the distinct phenotypes of germ-line, constitutive lineagespecific, and adult lineage-specific myostatin mutants are because of different modes of compensation.…”
Section: Discussionmentioning
confidence: 99%
“…10 Yet, germ-line inactivation of myostatin yielded conflicting results, describing no effect on cardiac hypertrophy or function 11,12 or reduced ejection fraction and eccentric hypertrophy. 13,14 Similarly, lineage-specific deletion of myostatin in cardiac progenitor cells revealed no differences in cardiac size and function in young mice, 15 whereas constitutive overexpression of myostatin in the heart 15 and in the heart and skeletal muscle 16,17 reduces cardiac mass and cardiomyocyte proliferation without effects on cardiac systolic function.…”
mentioning
confidence: 97%
“…The fact that we observed a decline in myostatin levels with age in the predominantly fast twitch extensor digitorum longus mus cle of mice, but a relative increase in myostatin levels in the slow twitch (type I) soleus, was therefore not anticipated. Nevertheless, it has been shown that mice lacking myostatin lose the same percent age of muscle mass with age as normal mice (Morissette et al, 2009), and muscles composed of different fiber types are all larger in aged myostatin deficient mice compared to those of same aged wild type mice (Jackson et al, 2012). Given that both myostatin levels and the myostatin:follistatin ratio increased with age in soleus muscles of mice compared to extensor digitorum longus, myostatin inhibitors may have a greater impact on preserving muscle mass with age in those muscles composed predominantly of slow rather than fast twitch fibers.…”
Section: Discussionmentioning
confidence: 99%